PENINGKATAN KEMAMPUAN BERBICARA DENGAN MENGGUNAKAN MEDIA GAMBAR SERI PADA SISWA KELAS I SDN 15 HALMAHERA SELATAN - Nurjana Kader; Samsu Somadayo; Darmawati Darmawati (PEDAGOGIK, 2021)
The purpose of this study was to improve the speaking ability of the first grade students of SD Negeri 15 South Halmahera Regency. The method used in this research is classroom action research. The source of the data intended in this research is the activities of students and teachers in speaking skills using serialized image media, especially Grade I students at SD Negeri 15 Halsel. The data collection procedures used in this study are (1) Test. The test was carried out twice, namely the initial test (pre-test) and the final test (post-test), (2) observations to measure student activity and researcher activities in the learning process, (3) interviews to find out the opinions or attitudes of students and teachers about their abilities. Students are being spoken to through the use of image media. Students Results: The use of serial image media in learning to speak is carried out in three stages, namely the planning, implementation, and evaluation stages. (1) The use of Serial Picture Media in learning can improve students' speaking skills, (2) Learning evaluation is carried out in two aspects, namely evaluation of the learning process, and evaluation of learning outcomes, (4) Overall, students' skills increased from an average of 61 in cycle 1 to 80 in cycle 2. The highest value in cycle 1 reaches 80, while in cycle 2, it increases to 90. While the lowest value in cycle 1 is 45, and in cycle 2 it increases to 75. (4) The percentage of complete learning students also increased from cycle 1 to cycle 2. This can be seen in the percentage of completeness in cycle 1 only reached 65%, while in cycle 2 it increased to 100%. Thus, the level of incompleteness decreased from 45% to 0%.